Good God but you smart! Language prejudice and upwardly mobile Cajuns - Stanford, Nichole E., author; Utah State University Press, publisher (Colorado State University. Libraries, 2016)
First comprehensive book in Composition Studies to examine educational and linguistic assimilation, as well as the local languages--Louisiana French and prevalent Cajun English--of Cajuns and explores the subtle ways grammar snobbery, from classrooms to families to pop culture references, is used to justify systemic inequality.--Provided by publisher.
Sexy ass Cajuns: the complicated reasons we comply -- Bas class: Cajuns and the U.S. class system -- "I will not speak French. i will not speak French": the grand derangement du langue -- Don't blame teachers (not too-too much): code censoring in classrooms -- Beyond classrooms: debunking the language myths.
Keywords: English language -- Dialects -- Social aspects; Sociolinguistics -- Louisiana; English language -- Dialects -- Louisiana